2022
DOI: 10.3390/foods12010117
|View full text |Cite
|
Sign up to set email alerts
|

Jabuticaba (Plinia sp.) Peel as a Source of Pectin: Characterization and Effect of Different Extraction Methods

Abstract: The peel of jabuticaba, a small fruit native to Brazil, has been shown to be a potential source of antioxidants and soluble dietary fibers. In this study, flours prepared from these peels were evaluated as a source of pectin. Different extraction methods were employed: ultrasound (US) extraction followed by low temperature heating (40 °C); in a microwave (MW) without (method 1) or with cellulase (method 2) or hemicellulase (method 3); or in a water bath (method 4). Pectin yields ranged from approximately 18% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Delphinidin-3- O -glucoside (D3G) was also identified ( Figure 2 A). These same compounds were also found in pectin extracted from jabuticaba peel flour [ 20 ]. Other compounds were separated during the chromatographic run, but could not be identified due to the absence of standard compounds.…”
Section: Resultsmentioning
confidence: 61%
“…Delphinidin-3- O -glucoside (D3G) was also identified ( Figure 2 A). These same compounds were also found in pectin extracted from jabuticaba peel flour [ 20 ]. Other compounds were separated during the chromatographic run, but could not be identified due to the absence of standard compounds.…”
Section: Resultsmentioning
confidence: 61%
“…[19] It was reported that the polysaccharides from jaboticaba fruit exhibit antitumor, anti-oxidant, and hypoglycemic activities. [20,21] However, current studies focused on the polysaccharides from jaboticaba fruit are mainly extracted by hot water extraction, few reports concerning on the polysaccharides extracted by UAE, an extraction method known to obtain polysaccharides with special structure and higher biological activities. Thus, it is necessary to explore the structural features and biological activities of jaboticaba fruit polysaccharides obtained using UAE method.…”
Section: Introductionmentioning
confidence: 99%
“…Jaboticaba fruit polysaccharide (MCP) is one of the main active ingredients of jaboticaba fruit [19] . It was reported that the polysaccharides from jaboticaba fruit exhibit anti‐tumor, anti‐oxidant, and hypoglycemic activities [20,21] . However, current studies focused on the polysaccharides from jaboticaba fruit are mainly extracted by hot water extraction, few reports concerning on the polysaccharides extracted by UAE, an extraction method known to obtain polysaccharides with special structure and higher biological activities.…”
Section: Introductionmentioning
confidence: 99%